What Is the Sense of Agency and Why Does it Matter? - Moore, James W. (Frontiers in Psychology, 2016)
Sense of agency refers to the feeling of control over actions and their consequences. In this article I summarise what we currently know about sense of agency; looking at how it is measured and what theories there are to explain it. I then explore some of the potential applications of this research, something that the sense of agency research field has been slow to identify and implement. This is a pressing concern given the increasing importance of ‘research impact’.